2011
DOI: 10.4111/kju.2011.52.7.485
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tamsulosin, Solifenacin, and Combination Therapy for the Treatment of Ureteral Stent Related Discomforts

Abstract: PurposeTo evaluate the effect of tamsulosin, solifenacin, and combination therapy of two agents in improving the lower urinary tract symptoms of patients with indwelling double-J ureteral stents.Materials and MethodsA total of 168 patients underwent placement of a double-J ureteral stent after retrograde ureteroscopy for urinary stone disease. All patients received polyurethane double-J ureteral stents (6 Fr, 24 or 26 cm), which were removed a mean of 14 days postoperatively. A total of 48 patients were given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 19 publications
4
50
1
Order By: Relevance
“…Alpha-blockers relieve flank pain by decreasing the muscle tone of the ureter, bladder trigone and prostatic urethra by blocking the alpha-adrenergic receptors and thus reducing bladder outlet resistance and pressure during micturition. Moreover, anticholi-nergics decrease bladder overactivity and contraction by mediating the muscarinic receptors, thereby reducing urinary symptoms (15,18). To the best of our knowledge, this is the first study showing that the combination of terazosin and tolterodine improved stent-related discomforts and decreased consumption of analgesics.…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…Alpha-blockers relieve flank pain by decreasing the muscle tone of the ureter, bladder trigone and prostatic urethra by blocking the alpha-adrenergic receptors and thus reducing bladder outlet resistance and pressure during micturition. Moreover, anticholi-nergics decrease bladder overactivity and contraction by mediating the muscarinic receptors, thereby reducing urinary symptoms (15,18). To the best of our knowledge, this is the first study showing that the combination of terazosin and tolterodine improved stent-related discomforts and decreased consumption of analgesics.…”
Section: Discussionmentioning
confidence: 68%
“…Previous studies (19,23) have shown no impact of anticholinergic on stent discomforts, whereas Lim et al (15) have demonstrated a reduction in the total IPSS in patients receiving solifenacin compared with those receiving no medication. We believe that the effect of tolterodine on urinary symptoms may be caused by either informing the patients about the possible increase in symptoms by activity that could reduce activities of daily living and consequent trigone irritation by the stent tail or blockade of muscarinic receptors by tolterodine.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…1. A total of 21 potentially eligible studies were identified and seven studies were subsequently excluded for not fulfilling the inclusion requirements, one of which was not a RCT (20). A Russian article published in Urologiia met the inclusion criteria according to the English abstract in PubMed; however it was subsequently excluded, since the full text could not be located (21).…”
Section: Resultsmentioning
confidence: 99%